Theoretical foundations of molecular magnetism - Boca, Roman (Current methods in inorganic chemistry, 1999)
Magnetochemistry is a highly interdisciplinary field that attracts the interest of chemists, physicists and material scientists. Although the general strategy of theoretical molecular magnetism has been in place for decades, its performance for extended systems of interacting magnetic units can be very complicated. Professor Boca's book treats the "mosaic" of the theoretical approaches currently used in the field. This book presents a review of the theoretical concepts of molecular magnetism. The first chapter of the book recapitulates the necessary mathematical background. An overview of macroscopic magnetic properties is then presented. Formulation of magnetic parameters and methods of their calculation are given, followed by a brief summary of magnetic behaviour. The core of the book deals with the temperature dependence of magnetic susceptibility for mononuclear complexes, dimers, and exchange-coupled clusters. This book will be particularly useful for those scientists and students working in the field of molecular magnetism who need to refer to a complete and systematic treatment of the mathematics of magneto-chemical theory